Introduction to Cell Agriculture, de Ahmed Khan - Jacobs, George (Ecolinguística: Revista brasileira de ecologia e linguagem (ECO-REBEL), 2019)
KHAN, Ahmed. Introduction to Cell Agriculture, ebook available at https://cellagri.mykajabi.com/ebook